Psychometric properties of the traditional Chinese version of the COVID Stress Scales in Hong Kong - Ng, Ting Kin; Chan, Wai; Wang, Kitty Wan Ching (Frontiers in Public Health, 2023)
Introduction: The COVID Stress Scales (CSS) assess six domains of COVID-19-related stress, including (a) COVID danger, (b) COVID socioeconomic consequences, (c) COVID xenophobia, (d) COVID contamination, (e) COVID traumatic stress symptoms, and (f) COVID compulsive checking. Although the CSS have been validated in various cultural contexts, their psychometric properties in Hong Kong have not been examined. This study endeavors to validate the traditional Chinese version of the 36-item CSS (CSS-36) and the 18-item CSS (CSS-18) in Hong Kong. Method: Participants were 521 Hong Kong undergraduate students (61% female) aged from 18 to 26 years (M = 20.65, SD = 1.56). An online questionnaire was used for data collection. Results: The results of confirmatory factor analyses supported a six-factor structure for both the CSS-36 and the CSS-18. Multiple-group confirmatory factor analyses established the gender invariance of the six-factor model for both the CSS-36 and the CSS-18. The CSS-36 and the CSS-18 exhibited good internal consistency reliability and concurrent validity with fear of COVID-19 and negative emotional states. Discussion: The findings offer evidence for the psychometric properties of the traditional Chinese version of the CSS-36 and the CSS-18 in the Hong Kong context.